If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8(n-2)=-10+5n
We move all terms to the left:
-8(n-2)-(-10+5n)=0
We add all the numbers together, and all the variables
-8(n-2)-(5n-10)=0
We multiply parentheses
-8n-(5n-10)+16=0
We get rid of parentheses
-8n-5n+10+16=0
We add all the numbers together, and all the variables
-13n+26=0
We move all terms containing n to the left, all other terms to the right
-13n=-26
n=-26/-13
n=+2
| .4(−3−6a)=36 | | 3(2x−5)−4x+8=−1 | | 4/5=r/2.5 | | -0.7(5x+3)=-3x-9 | | 8+6x=15x-1 | | 8+2t=26 | | -13c-10c-8c+6c+19c=-6 | | -5(-3r-3)=75 | | n²+n=132 | | 4(−3−6a)=36 | | (x)=4x+5(-8) | | 3x×78=81 | | 16r-11r-r=16 | | 6(x-1)=−72 | | -3n+18+7n=58 | | -12x-6=3x-6 | | (2t-1)/3=(3t+2)/15 | | 9(x-1)-9=6x+3(-5+x) | | 6x+7=-6+4x+21 | | -31=3v+9-8v= | | 1/5x=85 | | x2/3=90 | | 11.2d-12.72=13.6d | | -5(3x-3)+9x=6(x+4) | | 7x-6=-7+8 | | x1+x+2+x+3=45 | | 8(x-6)=-3(6-2x)+5x | | 4r-5=90 | | 40+1.50x=30 | | 12x+13=2x+93 | | 9-4(2x-1)=1-5x | | 27-7b=-6-2(1+6b) |